Emptiness in Teak (Tectona grandis L.) Fruits - Dabral, S. L. (Indian Forester, 1976)
Present study was undertaken to determine the stage at which the emptiness develops in teak fruits and to find out the possible reasons for it. Effects of factors like fertilisation of ovules, site age of the stand and skeletoniser attack were considered. It was found that in early stages teak fruits have a ovule in each of the loculi. Emptiness develops at the stage when the endocarp hardens due to heavy lignification in those loculi which have ovules in watery stage. The sizes of the loculi and the seeds are also determined at this stage. The emptiness is not related to the size or the loculi. Reserve food material accumulated during past growing seasons is utilised in seed formation . Site, which affects the availability of food, has significant effect on emptiness and should be taken into account while raising seed plots and orchards. Skeletoniser attack and the age of the stand (over 20 years) have no significant effect on emptiness.